Was The Telescope Obvious? An Inquiry Into Simultaneous Invention - Gratzinger, Peter (Science and Technology Law Review, 2012)
History is full of inventions that multiple people appear to have arrived at independently at about the same time, from the telescope (Lippershey, Metius, and others, 1608) to the telegraph (Morse, Steinheil, and others, 1837). Simultaneous independent invention is so common that some commentators have wondered if inventions are inevitable, the byproduct of existing culture rather than the work of individual genius. This philosophical problem has important practical implications in intellectual property law, which is deeply conflicted on the issue. On the one hand, the Patent and Trademark Office has procedures in place to award a patent to the winner of a race between two or more groups for the same invention. On the other hand, the Federal Circuit recently confirmed that simultaneous independent invention can indicate that the idea was obvious and nobody deserves to patent it. This Article explores this conflict, including recent case developments, and suggests a potential resolution.